Cyrtosperma hayii (Araceae, Lasioideae), a unique new species with downward-pointing spines from Southwest Papua Province, Indonesia - Raynalta, Erick; Hariri, Muhammad Rifqi; Irsyam, Arifin Surya Dwipa (Phytotaxa, 2024)
N/A